(untitled) (Vietnam Journal of Community Medicine, 2022)
Objective: Describe the actual safety situation at markets in Bac Ninh province and identify some related factors. Methods: A cross-sectional descriptive study from May 2020 to December 2020 from 384 food business establishments in 32 markets in Bac Ninh province. Results: 16.3% of unprocessed food sellers and 15.3% of processed food sellers owned food safety certificates. Unprocessed foods and processed foods at the markets were mainly grown in Bac Ninh province and purchased from households. The percentage of correct food safety knowledge was high, 72.5% in unprocessed foods and 70.8% in processed foods. However, the rate of good practice of food safety was low, only 25.8% in unprocessed foods and 16.7%. In the group of unprocessed foods, 81.9% of meat samples were contaminated with E.coli, of which 44.4% of samples contaminated with E.coli exceeded the allowable limit; 1.39% of samples detected banned substance salbutamol; 55.6% of fish and shrimp samples were found to be infected with E.coli, of which 4.17% of samples were infected beyond the allowable limit; 19 samples of fresh fruits and vegetables, instant fruit with residues of pesticides. Processed food group: 100% of salted vegetables and fruits samples contaminated with aerobic microorganisms exceeding the allowable limit; 97.9% samples of pork/spring rolls were contaminated with aerobic microorganisms; 93.6% samples of vermicelli/banh pho were contaminated with aerobic microorganisms. There is a statistically significant relationship between the practice of the pass food trader and the test results of the passed food samples.